2013
DOI: 10.1007/s10792-013-9849-9
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Vogt–Koyanagi–Harada disease with sensorineural hearing loss and choroidal thickening

Abstract: Purpose We report a case of Vogt-Koyanagi-Harada (VKH) disease that recurred with sensorineural hearing loss and choroidal thickening. MethodsWe measured the choroidal thickness using enhanced-depth imaging optical coherence tomography (EDI-OCT) in a patient with VKH during corticosteroid-tapering therapy.Results A 71-year-old man presented with fever, headache, and anorthopia associated with wavy choroidal folds and a serous retinal detachment (SRD). The EDI-OCT images showed choroidal thickening (> 600 μm at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In the present study, we revealed that the choroid also thickened during the anterior segment recurrence without any obvious findings in the posterior segment, and that this choroidal thickening had already been observed 1 month before detecting the recurrence. Although choroidal thickness alterations without any funduscopic findings have been examined in a few case reports,15 16 this study is the first case series to describe the detailed sequential changes in choroidal thickness in relation to the anterior recurrence of VKH disease.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we revealed that the choroid also thickened during the anterior segment recurrence without any obvious findings in the posterior segment, and that this choroidal thickening had already been observed 1 month before detecting the recurrence. Although choroidal thickness alterations without any funduscopic findings have been examined in a few case reports,15 16 this study is the first case series to describe the detailed sequential changes in choroidal thickness in relation to the anterior recurrence of VKH disease.…”
Section: Discussionmentioning
confidence: 95%
“…8 Others have shown that EDI-OCT can be used to detect not only recurrences in VKH, but also subclinical inflammation in the absence of overt intraocular inflammation detected on clinical examination. 28 While the prospects of using EDI-OCT in the management of VKH syndrome and other uveitides are promising, there is still much research to be done before new standards in clinical care can be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…While this can be accompanied by other ocular signs, such as anterior chamber cells and/or optic disc hyperfluorescence on FFA and/or dark dots on ICG,119 it can also precede them 47. Rebound choroidal thickening on EDI-OCT was the only sign of ocular inflammation in a 71-year-old patient who presented 6 months after his initial diagnosis with headache, tinnitus, and bilateral sensorineural hearing loss 120. Conversely, in chronic VKHD, sunglow fundus correlates with choroidal thinning on EDI-OCT scans 121.…”
Section: Historical Aspects and Epidemiologymentioning
confidence: 92%